QTL mapping reveals candidate genes for main agronomic traits in Luffa based on a high-resolution genetic map - Liu, Lili; Gan, Yaqin; Luo, Jianning; Li, Junxing; Zheng, Xiaoming; Gong, Hao; Liu, Xiaoxi; Deng, Liting; Zhao, Gangjun; Wu, Haibin (Frontiers in Plant Science, 2022)
Luffa is an important medicinal and edible vegetable crop of Cucurbitaceae. Strong heterosis effects and strikingly complementary characteristics were found between the two domesticated Luffa cultivars, Luffa acutangula and Luffa cylindrica. To explore the genetic basis underlying their important agronomic traits, we constructed the first interspecific high-density genetic linkage map using a BC1 population of 110 lines derived from a cross between S1174 (Luffa acutangula) and P93075 (Luffa cylindrica). The map spanned a total of 2246.74 cM with an average distance of 0.48 cM between adjacent markers. Thereafter, a large-scale field-based quantitative trait loci (QTLs) mapping was conducted for 25 important agronomic traits and 40 significant genetic loci distributed across 11 chromosomes were detected. Notably, a vital QTL (qID2) located on chromosome 9 with a minimum distance of 23 kb was identified to be responsible for the internode diameter and explained 11% of the phenotypic variation. Lac09g006860 (LacCRWN3), encoding a nuclear lamina protein involved in the control of nuclear morphology, was the only gene harbored in qID2. Sequence alignment showed completely different promoter sequences between the two parental alleles of LacCRWN3 except for some nonsynonymous single nucleotide polymorphisms (SNPs) in exons, and the expression level in thick-stem P93075 was distinctively higher than that in thin-stem S1174. According to the natural variation analysis of a population of 183 inbred lines, two main haplotypes were found for LacCRWN3: the P93075-like and S1174-like, with the former haplotype lines exhibiting significantly thicker internode diameters than those of the latter haplotype lines. It showed that LacCRWN3, as the only CRWN3 gene in Cucurbitaceae, was the most likely candidate gene regulating the internode diameter of Luffa. Our findings will be beneficial for deciphering the molecular mechanism of key phenotypic traits and promoting maker-assisted breeding in Luffa.